Pengaruh Literasi Keuangan Syariah dan Lingkungan Sosial KJKS Arjuna Terhadap Minat Menabung Santri Putri Pondok Pesantren Ngalah Pasuruan - Sukamto (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This study aims to determine the effect of Islamic Financial Literacy and Social Environment on the Savings Interest of female students in the Islamic Financial Services Cooperative (KJKS) Arjuna. The method used in this study is using quantitative methods with multiple linear regression and using data collection techniques through questionnaires. The population in this study were female students of dorm I Islamic boarding school Ngalah. Based on the results of this study, it can be concluded that Islamic financial literacy has a significant effect on saving interest in female students at the Arjuna Islamic Financial Services Cooperative (KJKS). This is indicated by the Tcount value of 3.531 while Ttable of 1.998 so that Tcount > Ttable (3.531 > 1.998) and a significant value of 0.000 <0.05 then H1 is accepted, the social environment has a significant effect on saving interest in female students in the Sharia Financial Services Cooperative (KJKS) Arjuna. This is indicated by the Tcount value of 5.690 while Ttable of 1.998 so that Tcount > Ttable (5.690 > 1.998) and a significant value of 0.001 < 0.05 then H2 is accepted, Islamic financial literacy and the social environment have a joint effect on the interest in saving female students in the Cooperative. Arjuna's Sharia Financial Services (KJKS) with Fcount of 16,029 while Ftable of 3.13, so the value of Fcount > Ftable or 16.029 > 3.13 then H3 is accepted